2019
DOI: 10.1101/804187
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary regain of lost gene circuit function

Abstract: Evolutionary reversibility -the ability to regain a lost function -is an important problem both in evolutionary and synthetic biology, where repairing natural or synthetic systems broken by evolutionary processes may be valuable. Here, we use a synthetic positivefeedback (PF) gene circuit integrated into haploid Saccharomyces cerevisiae cells to test if the population can restore lost PF function. In previous evolution experiments, mutations in a gene eliminated the fitness costs of PF activation. Since PF act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…This resource loading leads to a drop in the expression level of other genes, resulting in coupling between independently expressed genes and more generally to context-dependent gene expression. Moreover, squelching can be toxic to cells 34 , 36 38 and places a selective pressure against engineered circuits and the host cell, thus affecting both on evolutionary timelines 39 , 40 . As many established synthetic eukaryotic gene-regulation systems utilize TAs 14 , 17 , 41 44 , squelching is potentially a pervasive problem in eukaryotic synthetic biology.…”
Section: Introductionmentioning
confidence: 99%
“…This resource loading leads to a drop in the expression level of other genes, resulting in coupling between independently expressed genes and more generally to context-dependent gene expression. Moreover, squelching can be toxic to cells 34 , 36 38 and places a selective pressure against engineered circuits and the host cell, thus affecting both on evolutionary timelines 39 , 40 . As many established synthetic eukaryotic gene-regulation systems utilize TAs 14 , 17 , 41 44 , squelching is potentially a pervasive problem in eukaryotic synthetic biology.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic gene networks have been engineered to regulate drug resistance and have been shown to serve as well-characterized models of natural stress response modules in evolution experiments ( González et al, 2015 ; Bódi et al, 2017 ; Farquhar et al, 2019 ; Gouda et al, 2019 ).…”
Section: Synthetic Drug Resistance Gene Network and Antimicrobial Rementioning
confidence: 99%
“…The authors found an optimum on the fitness landscape that balances the costs and benefits of expressing a drug resistance gene in various experimental antibiotic inducer and drug conditions. In a subsequent microbial evolution study using the same positive feedback yeast strain, it was found that the synthetic gene network was fine-tuned by evolution to modulate the network’s noisy response and optimize fitness via specific “intra-circuit” and “extra-circuit” DNA mutations ( González et al, 2015 ), which can lead to loss of gene circuit function that can be regained in certain conditions under drug selection ( Gouda et al, 2019 ). The study by Gouda et al (2019) also suggests that slow growth due to antibiotics may allow cells to access hidden drug-resistant states prior to genetic changes.…”
Section: Synthetic Drug Resistance Gene Network and Antimicrobial Rementioning
confidence: 99%
See 2 more Smart Citations